Mitigating Violence Against First Responder Teams: Results and Ideas From the Hackmanathon. (June 2020) - Allen, Joseph A.; Taylor, Jennifer; Murray, Regan M.; Kilcullen, Molly; Cushenbery, Lily; Gevers, Josette; Larson, Lindsay; Ioku, Tomohiro; Maupin, Cynthia; Perry, Samantha; Park, Semin; Rosen, Michael; et al.
First responders are on the front line of patient care and service, but research has shown that they are also on the front line of exposure to violence. Currently, there is a lack of evidence-based interventions that prepare first responders to handle violence on the job. With the increase in emergency medical services (EMS) call volume and reports of at least 57% of the EMS responders having experienced workplace violence, there is a need to develop scientifically systematic solutions to improve emergency responder safety. Using an adapted version of the hackathon method, academic scholars and practitioner conference attendees at the Interdisciplinary Network for Group Research (INGRoup) Conference were deployed into three multidisciplinary teams to analyze the issue and develop specific solutions. These solutions offer unique interventions to improve first responder safety.